The High Court and the Constitution - Zines, Leslie (The Federation Press, 2008)
It is over eleven years since the fourth edition of the book was published by Butterworths (LexisNexis). This new 5th edition therefore includes information, analysis and critique of the High Court's jurisprudence during that period